(untitled) (Journal of Creative Industry and Sustainable Culture, 2022)
Soccer (or association football) is now the most popular sports game in the world. Various underlying factors may explain its reasons to be popular. However, there is no underlying explanation as to why the nature of the game processes was appealing to all people of all ages. However, measuring such subjective metric were empirically challenging and costly. In this paper, a mathematical model of a soccer game is established based on the game refinement theory, where the internal processes of a soccer game are explored where interpretation based on the “antagonistic rate” is established. Based on such measures, two stages were identified in the soccer game, and various soccer leagues’ data were utilized as the testbed. Further analysis of the soccer game was determined based on physics in mind measure using correspondence of Newtonian law of motions. These measures provide insights into the game stages’ underlying entertainment value, as well as a new perspective on the soccer game attractiveness.